2022
DOI: 10.1177/00469580221144398
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Illness of COVID-19 and Its Consequences on Health and Economic System

Abstract: The outbreak of COVID-19 has had destructive influences on social and economic systems as well as many aspects of human life. In this study, we aimed to estimate the economic effects of COVID-19 at the individual and societal levels during a fiscal year. This cost of illness analysis was used to estimate the economic burden of COVID-19 in Iran. Data of the COVID-19 patients referred to the hospitals affiliated to Bushehr University of Medical Sciences in 2021 were collected through the Hospital Information Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
4
9
0
Order By: Relevance
“…Our study found that COVID-19 has increased the indirect (absenteeism) costs of patients, which is consistent with the results of other studies in this regard 15–18 . The study by Faramarzi et al 7 on 1958 healthcare workers also reported a significant increase in absenteeism costs due to COVID-19.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study found that COVID-19 has increased the indirect (absenteeism) costs of patients, which is consistent with the results of other studies in this regard 15–18 . The study by Faramarzi et al 7 on 1958 healthcare workers also reported a significant increase in absenteeism costs due to COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…7,[15][16][17] Our study found that COVID-19 has increased the indirect (absenteeism) costs of patients, which is consistent with the results of other studies in this regard. [15][16][17][18] The study by Faramarzi et al 7 on 1958 healthcare workers also reported a significant increase in absenteeism costs due to COVID-19. A study by Maltezou et al 16 in Greece also reported that COVID-19 has increased the work absenteeism cost of healthcare personnel.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations